Thorough in silico and in vitro cDNA analysis of 21 putative BRCA1 and BRCA2 splice variants and a complex tandem duplication in BRCA2 allowing the identification of activated cryptic splice donor sites in BRCA2 exon 11. Issue 4 (22nd January 2018) - Baert, Annelot; Machackova, Eva; Coene, Ilse; Cremin, Carol; Turner, Kristin; Portigal‐Todd, Cheryl; Asrat, Marie Jill; Nuk, Jennifer; Mindlin, Allison; Young, Sean; MacMillan, Andree; Van Maerken, Tom; et al.
Abstract: For 21 putative BRCA1 and BRCA2 splice site variants, the concordance between mRNA analysis and predictions by in silico programs was evaluated. Aberrant splicing was confirmed for 12 alterations. In silico prediction tools were helpful to determine for which variants cDNA analysis is warranted, however, predictions for variants in the Cartegni consensus region but outside the canonical sites, were less reliable. Learning algorithms like Adaboost and Random Forest outperformed the classical tools. Further validations are warranted prior to implementation of these novel tools in clinical settings. Additionally, we report here for the first time activated cryptic donor sites in the large exon 11 of BRCA2 by evaluating the effect at the cDNA level of a novel tandem duplication (5′ breakpoint in intron 4; 3′ breakpoint in exon 11) and of a variant disrupting the splice donor site of exon 11 (c.6841+1G > C). Additional sites were predicted, but not activated. These sites warrant further research to increase our knowledge on cis and trans acting factors involved in the conservation of correct transcription of this large exon. This may contribute to adequate design of ASOs (antisense oligonucleotides), an emerging therapy to render cancer cells sensitive to PARP inhibitor and platinum therapies. Abstract : Evaluation of 21 putative BRCA1/2 splice site variants by RT‐PCR showed aberrant splicing for 12 variants. Our data suggest that learning algorithms such as Adaboost and Random Forest outperform classic splice prediction tools and warrant further validation. Additionally, we report the activation of cryptic donor sites in the large exon 11 of BRCA2 through cDNA analysis of a novel tandem duplication with its 3′ breakpoint in exon 11 and a variant disrupting the splice donor site of exon 11.